Nanostructural defects on surface and in bulk iduced with irradiation in LiF-O crystals - Dauletbekova, A.; Akilbekov, A.; Abdrakhmetova, A.; Russakova, A.; Baizhumanov, M.; Umatova, Z. (Recent Contributions to Physics, 2012)
Evolution of structure defects were investigated in LiF -O crystals irradiated at room temperature with 117 МеV 84Kr ions with a beam current of 10nA/cm2 in the fluence range 1011 - 1014 cm2 at the cyclotron accelerator DC-60 (Astana, Kazakhstan) and electron beam (0,2 Mev energy of electrons, the pulse duration 10ns). At the fluence of 1011 cm2, SEM imaging revealed mainly formation of etchable ion tracks. Above this fluence, severe structural modifications in the irradiated layer were observed which include the ion-induced formation of dislocations and grains with nano-scale dimensions. Nanostructures were not observe at electron irradiation.